Acute and subacute toxicity assessment of liquid CO2 extract of Phaleria macrocarpa fruits flesh in mice model - Mia, Abdur Rashid; Ahmed, Qamar Uddin; Helal Uddin, A.B.M.; Ferdosh, Sahena; Siddique, Monowarul Mobin; Hejaz Azmi, Syed Najmul; Ahmed, Jahangeer; Sarker, Md. Zaidul Islam (Elsevier, 2022)
Objectives Phaleria macrocarpa (Scheff.) Boerl., an evergreen tree is found in Indonesia, Malaysia and Oceania, explicitly Northern Territory of Australia and Papua New Guinea. The fruits are traditionally used to treat various ailments including diabetes, psoriasis, looseness of the bowels, skin inflammation, malignancy, kidney, liver and heart sicknesses. However, to date, no comprehensive study investigating its toxicity profile utilizing liquid CO2 extract (LCE) has been reported in ICR mice. Hence, this research was performed to investigate the both acute and sub-acute toxicities of the liquid carbon dioxide extract from ripe fruit flesh of the P. macrocarpa in mice.